The Development and Validation of HPLC-UV method for Analysis of Ciprofloxacin in serum and aqueous Humour - Abbas khan1, Zafar Iqbal1 , Jamshaid Ali Khan1, Muhammad Imran Khan1, Ghulam Sarwar khan2 Muhammad Bilal3, Tahir Mehmood Khan4 (Archives of Global Professionals, 2011)
A simple bioanalytical reversed phase HPLC method for thedetermination of the ciprofloxacin in serum, aqueous humourand ophthalmic drops was developed and validated. HPLCequipped with Hypersil C18 Column was operated in isocraticmode using acetonitrile and 0.25 M H3PO4 (60:40 v/v) asmobile phase that was pumped at rate of 1ml.min-1 and eluentswere monitored using UV-Visible detector at 275 nm. TheCiprofloxacin was analysed in serum, aqueous humour andophthalmic drops using acetaminophen as an internal standard(IS). The instrumental response was linear in the concentrationrange of 5 ng.ml-1 to 75 ng.ml-1 in aqueous humour and 10ng.ml-1 to 70 ng.ml-1 in serum. The LOD and LOQ, precision andreproducibility of the method were good for pharmacokineticsstudies.